Institute of Proof in the Criminal Proceedings of Russia: History and Modernity - EVGRAFOVA, Irina V.; MARCHENKO, Alexander V.; TRAVIN, Alexander V.; ZHULEV, Sergei K.; PROKOFEVA, Svetlana M. (Journal of Advanced Research in Law and Economics, 2019)
The institute of proofs is one of the most important institutions in criminal proceedings. Thanks to the proofs, the circumstances of the crimes commission are clarified, the persons who committed them are identified, sentences are imposed and justice is administered. The institute of proofs has an ancient history, calculated from the moment of the appearance of the trial as such. The aim of the article was to analyze the development of the institution of proofs in criminal proceedings in Russia. The article compares the proofs that existed in the ancient period of the Russian state with the proofs used in modern reality. The paper investigates the difference between these kinds of proofs, the reasons for their transformation throughout history and the main ways to improve the institution of proofs in the future. It was concluded that the establishment of proofs in Russia, as well as criminal proceedings in general, took place, on the one hand, during the reception of Roman law, and on the other hand, during the development of feudal social relations, which influenced the formation of kinds of proofs and methods for their preparation.